Brusatol Derivative–34 Attenuates Allergic Airway Inflammation Via Inhibition of the Spleen Tyrosine Kinase Pathway - Ding, Yasi; Tang, Weibin; Pei, Fei; Fu, Lixia; Ma, Pei; Bai, Jinye; Lin, Mingbao; Liu, Yunbao; Hou, Qi (Frontiers in Pharmacology, 2021)
Brusatol derivative-34 (Bru-34), a derivative of brusatol, has been shown significantly anti-inflammatory activity in mice in our previously work. However, to our knowledge, there were very limited studies on how Bru-34 affected airway inflammation. Thus, in this present study, the effects and potential mechanisms of Bru-34 on allergic airway inflammation were examined both in vivo and in vitro. The results showed that Bru-34 attenuated the allergic airway inflammation in mice, with significant decreasing of the inflammatory cells and mediators in bronchoalveolar lavage fluids and attenuation of the histopathological alterations in the lung tissues. In addition, Bru-34 significantly inhibited the release of inflammatory cytokines in antigen induced rat basophilic leukemia -2H3 (RBL-2H3) cells. What’s more, Bru-34 significantly decreased the expression of spleen tyrosine kinase (Syk), p-Syk, cytoplasmic phospholipase A2 (cPLA2), p-cPLA2, nuclear factor-κB (NF-κB) and p-NF-κB both in allergic mice lung tissue and antigen induced RBL-2H3 cells. Furthermore, the collaborative effects of Bru-34 with inhibitors against Syk, cPLA2, and NF-κB, showed that Syk was an important target of Bru-34, and cPLA2 and NF-κB played important roles in the coordinated inflammatory response. In conclusion, Bru-34 could significantly modulate the allergic airway inflammation, and its potential mechanism was revealed at least partially via down-regulating of Syk-cPLA2 -NF-κB signaling.